2019
DOI: 10.1371/journal.pone.0218656
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane cultivar response to glyphosate and trinexapac-ethyl ripeners in Louisiana

Abstract: Sugarcane ripening in Louisiana is necessary to ensure adequate sucrose levels in early-season harvested sugarcane. The response of nine sugarcane cultivar’s yield components to glyphosate and trinexapac-ethyl ripeners was determined in field trials. Glyphosate (210 g ae ha -1 ) and trinexapac-ethyl (200 g ai ha -1 ) treatments failed to increase sucrose yields more than non-ripened sugarcane. Sugarcane ripened with glyphosate or trinexapac-ethyl increased theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Sugarcane is a major agricultural crop in China, which as a country provides ∼80% of sugar produced globally (Chen et al, 2019), the second largest bioenergy crop in the world (Tomes et al, 2011). Sucrose is stored in the sugarcane stem and shoot height is an important determinant of sugar yield (Spaunhorst et al, 2019). Shoot length in graminaceous plants is largely determined by internode elongation, which is controlled the genetic make-up (Qi et al, 2011;Li et al, 2012), environmental factors (Mazzella et al, 2000;Peralta et al, 2002), and hormonal interactions (Buck-Sorlin et al, 2005;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane is a major agricultural crop in China, which as a country provides ∼80% of sugar produced globally (Chen et al, 2019), the second largest bioenergy crop in the world (Tomes et al, 2011). Sucrose is stored in the sugarcane stem and shoot height is an important determinant of sugar yield (Spaunhorst et al, 2019). Shoot length in graminaceous plants is largely determined by internode elongation, which is controlled the genetic make-up (Qi et al, 2011;Li et al, 2012), environmental factors (Mazzella et al, 2000;Peralta et al, 2002), and hormonal interactions (Buck-Sorlin et al, 2005;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On years where conditions favor natural ripening of sugarcane, there is frequently little or no response of sugarcane to ripener application. In a similar study, Spaunhorst et al (2019) reported an increase in TRS of 9% in glyphosate-treated Ho 07-613 over the nontreated control.…”
Section: Chemical Ripener Testsmentioning
confidence: 76%
“…The sucrose concentrations for cultivars L 01-299 and HoCP 96-540, the two most planted sugarcane cultivars in Louisiana, were among the most responsive (11-17% increase) and are considered highly responsive to glyphosate (Orgeron et al, 2019;Spaunhorst et al, 2019). Unfortunately, some cultivars treated with glyphosate ripener are shorter, and a reduction in sugarcane biomass may result from a glyphosate application (Spaunhorst et al, 2019). Orgeron et al (2019) reported that HoCP 00-950 responded moderately to glyphosate ripener.…”
Section: Chemical Ripener Testsmentioning
confidence: 99%